-3x-6(5x+8)=114

Simple and best practice solution for -3x-6(5x+8)=114 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-6(5x+8)=114 equation:


Simplifying
-3x + -6(5x + 8) = 114

Reorder the terms:
-3x + -6(8 + 5x) = 114
-3x + (8 * -6 + 5x * -6) = 114
-3x + (-48 + -30x) = 114

Reorder the terms:
-48 + -3x + -30x = 114

Combine like terms: -3x + -30x = -33x
-48 + -33x = 114

Solving
-48 + -33x = 114

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '48' to each side of the equation.
-48 + 48 + -33x = 114 + 48

Combine like terms: -48 + 48 = 0
0 + -33x = 114 + 48
-33x = 114 + 48

Combine like terms: 114 + 48 = 162
-33x = 162

Divide each side by '-33'.
x = -4.909090909

Simplifying
x = -4.909090909

See similar equations:

| 0.1y=-0.5x-1.7 | | Y=10-2y-8 | | 8/x=14/17 | | p=-0.001x^2-0.2x+12 | | 2/1=20/n | | -162=-2x+4(3x-18) | | 8/x=14/27 | | -26/9*3/2 | | 3x-4(-5x+14)=-171 | | y=2x-3sqrtx | | X/2/3=36 | | 5x-4y+15=0 | | -3x-2(5x-11)=113 | | 7/8=z/12 | | 7t-1=7t-5 | | -14/8= | | 1g-9=19 | | 8/4=n/12 | | 0.5x+7= | | 3x^2+12x=-3 | | x/12=24/26 | | 4/9-10/3 | | 32=6x-2(4x-8) | | (8x-7)+(8x+10)= | | K*7.50=123.75 | | .99=0.3n | | -4x-5(-5x+9)=60 | | 1.30*3.5=x | | -2(2x+1)=-2 | | 2b+5whenb=7 | | Y=x^5+4x^2-6x^6+7x^2-6x^0 | | 2.5*7.5=x |

Equations solver categories